Predictors of survival after operation among patients with large cell neuroendocrine carcinoma of the lung - Eichhorn, Florian; Dienemann, Hendrik; Muley, Thomas; Warth, Arne; Hoffmann, Hans (The annals of thoracic surgery, 2015)
Background - Large cell neuroendocrine carcinoma (LCNEC) represents a rare entity in non-small cell lung cancer, with only partially understood biology and poor survival. A diagnosis is difficult to obtain on the basis of small biopsy specimens, but surgical procedures may be indicated in only a small fraction of patients. The aim of this study was to assess the clinical and immunohistochemical features of patients with LCNEC to identify predictors of outcome and long-term survival. - Methods - The clinical and pathologic data of 57 surgical patients with LCNEC between March 2003 and December 2012 were retrospectively reviewed. The tumor specimens were examined for expression of neuronal specific enolase, synaptophysin, CD 56, chromogranin-A, and the somatostatin receptor by immunohistochemistry. Statistical analysis was performed to determine significant predictors for overall survival and recurrence-free survival. - Results - Fifty-seven patients (41 men, 16 women) underwent thoracic operations with curative intent. Complete resection was achieved in 91% of cases. The results of staining for CD56, synaptophysin, neuronal specific enolase, chromogranin-A, and somatostatin were positive in 86%, 81%, 68%, 61%, and 21%, respectively. Recurrence occurred in 28 patients (49%). Overall survival and recurrence-free survival were 50% and 45%, respectively, after 3 years. Advanced nodal status (N1, p < 0.025; N2, p < 0.02) and simultaneous expression of CD56 and chromogranin-A (p < 0.04) were significantly associated with poorer outcome. - Conclusions - LCNEC is a rare neuroendocrine pulmonary malignancy that is associated with poor prognosis and high recurrence rates. Surgical treatment can achieve satisfactory results in selected cases. Neuroendocrine marker profiles may predict prognosis and may influence the decision for adjuvant therapy or follow-up intervals.